Pengenalan Healthy Nutritious Food Knowledge dan Personal Hygiene di SD Negeri Gadingsari, Kecamatan Binakal, Kabupaten Bondowoso - Puspito, Agung Nugroho; Ubaidillah, Mohammad; Widyawati, Arista; Nabyla, Cahyani Farhatin; Amami, Nurillah Adi Aurura; Herlambang, Yasina Alhadila Nazima (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2025)
Children's ability to eat healthy and nutritious food is closely related to education. Education is an inseparable process as an effort to grow and develop the potential in every human being. Especially in children, education plays an important role in forming a healthy diet and good hygiene behavior. However, in several studies in Indonesia, it is not uncommon to find that there is still a lack of knowledge about healthy and nutritious food and good hand washing among elementary school students which harms their health. As in SDN Gadingsari, Binakal District, there are still many elementary school students who have a low understanding of healthy and nutritious food. The author's purpose in carrying out this social project is to socialize, provide education and understanding directly to SDN Gadingsari students about the importance of eating healthy and nutritious food and good hygiene behavior through interactive learning such as showing videos as a result of eating nutritious healthy food, washing hands, providing material on the concept of the contents of my plate, the content in nutritious food such as carbohydrates, protein, fat, fiber, vitamins, and minerals, games to gymnastics together. The results showed that the students were very enthusiastic about learning about healthy and nutritious food. It is hoped that students can apply it in their daily lives.